Perempuan Pejuang Sutra di Kabupaten Wajo: Aktor Tunggal dan Tantangan Akses Program Perhutanan Sosial - Sukma taroniarta; Nurul Huda Yahya (Jurnal Perempuan, 2022)
Silk is a symbol of cultural grandeur in South Sulawesi. Complex business issues, and lifestyle changes within communities, has led to the silk industry being vulnerable to abandonment. Social Forestry, through a scheme to increase non-timber forest product businesses on community lands, can provide economic opportunities for silk-based businesses, which are dominated by women. This study is a qualitative study supported by quantitative data. Direct observations and in-depth interviews were conducted with several key figures in the silk business in Canru Village, Wajo Regency, South Sulawesi. The results of the study show that economic pressure is the main motivation for shifting roles in the silk business, but there are several other obstacles that threaten the sustainability of the silk industry, which has lasted for hundreds of years.